The effect of a complex training and detraining programme on selected strength and power variables in early pubertal boys - Ingle, L.; Sleap, M.; Tolfrey, K. (Journal of Sports Sciences, 2006)
Complex training, a combination of resistance training and plyometrics is growing in popularity, despite limited support for its efficacy. In pre- and early pubertal children, the study of complex training has been limited, and to our knowledge an examination of its effect on anaerobic performance characteristics of the upper and lower body has not been undertaken. Furthermore, the effect of detraining after complex training requires clarification. The physical characteristics (mean±s) of the 54 male participants in the present study were as follows: age 12.3 ± 0.3 years, height 1.57 ± 0.07 m, body mass 50.3 ± 11.0 kg. Participants were randomly assigned to an experimental (n = 33) or control group (n = 21). The training, which was performed three times a week for 12 weeks, included a combination of dynamic constant external resistance and plyometrics. After training, participants completed 12 weeks of detraining. At baseline, after training and after detraining, peak and mean anaerobic power, dynamic strength and athletic performance were assessed. Twenty-six participants completed the training and none reported any training-related injury. Complex training was associated with small increases (=5.5%) in peak and mean power during training, followed by decreases of a similar magnitude (= -5.9%) during detraining (P < 0.05). No changes or minor, progressive increases (=1.5%) were evident in the control group (P > 0.05). In the experimental group, dynamic strength was increased by 24.3 - 71.4% (dependent on muscle group; P < 0.01), whereas growth-related changes in the control group varied from 0 to 4.4% (P > 0.05). For 40-m sprint running, basketball chest pass and vertical jump test performance, the experimental group saw a small improvement (=4.0%) after training followed by a decline (= -4.4%) towards baseline during detraining (P < 0.05), whereas the control group experienced no change (P > 0.05). In conclusion, in pre- and early pubertal boys, upper and lower body complex training is a time-effective and safe training modality that confers small improvements in anaerobic power and jumping, throwing and sprinting performance, and marked improvements in dynamic strength. However, after detraining, the benefits of complex training are lost at similar rates to other training modalities.